Prevalence and Severity of Dental Cavities in Adolescents - Leticia Espinosa González; Indira Gómez Capote; María de la Caridad Barciela González- Longoria; Rosa María González Ramos (Revista Cubana de Estomatología, 2024)
Introduction: Dental cavities is a multifactorial disease prevalent during childhood and adolescence.